A Framework for Digital Image Encryption using Chaotic Baker Map with SHA Algorithm - Saravanan, S; Sivabalakrishnan, M (International journal of innovative technology and exploring engineering, 2019)
Recently, security for the image is becoming very important. Image Encryption is the only choice in protecting the digital image by transforming the image into an unreadable format. There are many methods used to protect against unauthorized access. This research proposes a framework for image encryption using Chaos Baker map with SHA-1 algorithm. The Chaotic Baker map is a randomization technique used to make the pixels more shuffled. Key generation is essential part of image encryption, which will be carried out by SHA-1 algorithm. Experimental results show that the proposed method is well suited for high security, key sensitivity and resists various attacks.